A SENSITIVE KINETIC SPECTROPHOTOMETRIC DETERMINATION OF TRACES OF TUNGSTEN IN SOLUTION BASED ON ITS INHIBITORY EFFECT ON THE DECOLORIZATION REACTION OF POTASSIUM PERMANGANATE - Petković, Branka; Micić, Ružica; Simonović, Ranko (Bulletin of Natural Sciences Research, 2016)
The present work describes a rapid and sensitive method for the determination of ultramicro amounts of tungsten (VI) based on its inhibitory effect on the oxidation of 4-hidroxycoumarine by potassium permanganate in the presence of hydrochloric acid. The sensitivity of the method is 20 ng/cm3. The probable relative error is -4.8-13 % for the W(VI) concentration range 250 to 20 ng/cm3, respectively. Kinetic equations for the investigated process which determine the order of the reactions regarding to each reaction parameter under certain experimental conditions were proposed, and they allowed quantification of the unknown concentrations W(VI) in solution. The detection and quantification limit of the method are 4.5 and 15.1 ng/cm3. The effects of certain foreign ions upon the reaction rate were determined for the assessing the selectivity of the method.
Keywords: 4-hidroxycoumarine; tungsten(VI); inhibition; spectrophotometric determination; Kinetic method